Besarnya Gaya Radial Yang Terjadi Pada Sepasang Roda Gigi Lurus Akibat Adanya Sudut Tekan Dari Roda Gigi Penggerak Di Alat Double Deck Bunch Crusher - Hariski Panggabean; Herry Darmadi (CV MEDAN TEKNO SOLUSI, 2023)
Gears are machine elements whose function is to transmit power and rotate the shaft so that the machine mechanism system can work with its function. Straight gears are used for parallel or parallel shafts. Straight gears are used to drive the rollers in the Double Deck Bunch Crusher. When two straight gears connected to each other rotate, a force arises from the two contacting gears, the straight gear A (the driving one) will press inwards towards the center point of the straight gear B (the driven one). The force acting on the straight gear is the Radial Force (Fr). Radial force is a force that acts perpendicular to the shaft axis which causes the two gears to push each other. The aim of this research is to determine the magnitude of the tangential force and radial force on a pair of straight gears when the Double Deck Bunch Crusher is operating. From the test results, it was found that the tangential force in the pair of straight gears at the top was 263747.629 kg and the tangential force in the pair of straight gears at the bottom was 282444.157 kg while the radial force in the pair of straight gears at the top was 95996.286 kg and the radial force in the pair of straight gears at the bottom is 102801.265 kg.